Tennessee Williams And The Theatre Of Excess : The Strange, The Crazed, The Queer - Saddik, Annette J., 1966- author (2015)
xi, 180 pages : 24 cm | "The plays of Tennessee Williams' post-1961 period have often been misunderstood and dismissed. In light of Williams' centennial in 2011, which was marked internationally by productions and world premieres of his late plays, Annette J. Saddik's new reading of these works illuminates them in the context of what she terms a "theatre of excess," which seeks liberation through exaggeration...
Droits : Selon les droits indiques dans Internet Archive
Keywords: internet archive; livre; histoire; Géographie; bibliotheque numerique; Histoire